Understanding The Christian Community's Stance Towards The Muslim Community In Sabah: After The Ban On The Usage Of The Term Allah. - Abd Hakim Mohad @ Mohamad Ramli; Yusten Karulus; Saini Ag Damit; Mohd Sohaimi Esa; Dayu Sansalu; Ros Aiza Mohd Mokhtar; Ahmad Tarmizi Talib; Sarjit S. Gill (Human Resource Management Academic Research Society, 2024)
Non-Indexed Publication